Communal utopias and the American experience : secular communities, 1824-2000 - Sutton, Robert P. (Praeger Publishers, 2004)
This important study begins with America's first secular utopia at New Harmony in 1824 and traces successive utopian experiments in the United States through the following centuries. For the first time, readers will come to realize that American communalism is not a disjointed, erratic, almost ephemeral part of our past, but has been an on-going, essential part of American history. We have a communal utopian motif that sets the history of the United States apart from any other nation. The utopian communal story is just one other dimension of the Puritan concept that America was a city upon a h.